The Role of Business Mentors in Assisting the Growth of Education-Supported MSMEs - Sutrisno Sutrisno (Indo-MathEdu Intellectuals Journal, 2023)
MSMEs play a crucial role in a country's economy. They contribute to job creation, local economic growth, and product or service innovation. Education is also recognised as a key pillar in community and economic development. Improving the quality of education has the potential to help MSMEs grow and thrive. The purpose of this study is to examine the role of business mentors in supporting the growth of MSMEs that receive support from education. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from special sources, namely Google Scholar and Google search engine. The results of this study show that the role played by business mentors in supporting the growth of education-supported MSMEs is significant. The collaboration between business knowledge gained through formal education and practical guidance from mentors forms a strong foundation for sustainable business growth. Mentors not only provide insight and experience, but also help young business owners overcome challenges, formulate effective strategies, and build valuable networks. In an ever-changing business ecosystem, this role is becoming increasingly important in moulding the next generation of competent and innovative entrepreneurs.